Future Computer, Communication, Control and Automation - Zhang, Tianbiao (Advances in Intelligent and Soft Computing, 2012)
The volume includes a set of selected papers extended and revised from the 2011 International Conference on Computer, Communication, Control and Automation (3CA 2011). 2011 International Conference on Computer, Communication, Control and Automation (3CA 2011) has been held in Zhuhai, China, November 19-20, 2011. This volume topics covered include wireless communications, advances in wireless video, wireless sensors networking, security in wireless networks, network measurement and management, hybrid and discrete-event systems, internet analytics and automation, robotic system and applications, reconfigurable automation systems, machine vision in automation. We hope that researchers, graduate students and other interested readers benefit scientifically from the proceedings and also find it stimulating in the process.